Tratamiento de la ética periodística en el género de opinión del programa "Corrientes de Opinión Ciudadana" en Radio Novedades de la ciudad de Latacunga - Egas Armas, Jorge Francisco (2016)
This research focuses on the analysis about gender opinion based on Ecuadorian Constitution rules and laws, deontological rules of the Communication Law and codes Radio and Television Ecuadorian Association in “Corrientes de Opinión Ciudadana” program transmitted by Radio -Novedades-1100 AM from Monday to Friday at 07:45 to 12:45 where social, cultural and political issues are addressed. Leonel Yánez, Oscar Aguilera, Orlando Villalobos, Rodrigo Santillán among others authors were taken as references, in relation to gender opinion in radio, which contributed significantly to the theoretical content of this research. Descriptive research was used to analyze the daily published contents in this program, in order to know if this program is under the rules of professional conduct and journalist ethics in radio, taking into account the objective of it is to educate inform and entertain its listeners. Who through the information issued generate public opinion of what happens province of Cotopaxi daily. Once collected the information step using techniques hidden observation and content analysis, where it can show concretely that this segment meeting within the parameters set by law, which see given information is issued correctly without discriminating or violate the people honor of and using the right language to go to the different type of audience that this has.